FINANCIAL AND ECONOMIC BASE OF LOCAL BUDGETS AS A KEY TO SUSTAINABLE REGIONAL DEVELOPMENT (INNOVATIVE ECONOMY, 2023)
Vatamanyuk-Zelinska U.Z., Matsei K.P. FINANCIAL AND ECONOMIC BASE OF LOCAL BUDGETS AS A KEY TO SUSTAINABLE REGIONAL DEVELOPMENTPurpose. The aim of the article is based on the assessment of the financial base of local budgets; identify key aspects of the formation and use of financial resources of territorial communities of Ukraine, offering effective approaches to managing the financial resources involved for local self-government bodies.Methodology of research. General scientific and special methods were used in the research process, in particular: dialectical, monographic, analysis and synthesis – to study the financial and economic basis of local budgets; comparative analysis – to compare economic indicators in time and space; abstract and logical – during the formation of theoretical generalizations, assumptions, conclusions.Findings. The need to intensify partnership cooperation between territorial communities, in the field of establishing communication and partnership relations between those territorial communities that have suffered as a result of military operations and those that can provide them with the necessary financial support, has been determined. It is proposed to adapt investment passports of regions and regional strategies of their development to the conditions of martial law.Originality. It is proposed to supplement the map of investment and business opportunities of Ukraine with separate requests for the restoration of infrastructure in the de-occupied Ukrainian territories in terms of already existing sectors. It is recommended to create a register of critical and social infrastructure objects for reconstruction and restoration with information on the nature of damage (destruction), the restoration project, volumes, sources and stages of financing in terms of planned and actual indicators.Practical value. Proposals based on research results can be used by local self-government bodies to restore critical infrastructure facilities, strengthen the financial and economic base of local budgets, which will contribute to the stabilization of regional development of Ukraine.Key words: budget, regional development, income, investments, borrowing.
Keywords: budget; regional development; income; investments; borrowing